Birth Order and Personality : Testing Assumptions with Independent Siblings' Reports - Franklin, Bethany R.; Johnson, Amy E.; Kelley, Jenna A. (My University, 2012)
Assumptions about the effects of birth order on personality abound in popular culture, self-help books, and the scholarly literature. Judith Rich Harris has proposed that, if birth order does affect individuals' behavior, it does so only within the family context. According to Harris, tactics that may be effective at home for a child of a given birth order are not necessarily going to be effective for that child in other contexts. There is no known study that has directly tested Harris' theory by assessing two adult siblings who were raised in the same home, and comparing their personalities as a function of their birth order. This study was designed with that specific objective, with the prediction (in accord with Harris' theory) that adult siblings' independent self-reports would not differ as a function of birth order.
Color poster with images, graphs, and tables.
Keywords: Birth order--Psychological aspects; Personality development--Social aspects; Families--Research; Posters